SELEKSI KEMAMPUAN BAKTERI PELARUT FOSFAT ASAL BUKIT BATU-RIAU DALAM MENGHASILKAN ASAM SIANIDA - Pristiana Aprillia; Delita Zul; Bernadeta Leni Fibriarti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Phosphate solubilizing bacteria (PSB) is beneficial bacteria which are not only capablein solubilizing organic phosphate into inorganic phosphate, but also producing cyanideacid (HCN). HCN plays a role in controling weed growth. The objective of this researchwas to screen the potency of indigenous PSB isolated from peat soil in producting HCN.The collections of PSB were subcultured in King’B broth. The ability of 152 isolates onHCN production were tested qualitatively using filter paper soaked with picric acid andNa 2 CO 3 . The result indicated that as many as 26 isolates (17.1%) were able to releasevarious levels of HCN production based on the appearing of brown, dark brown, orreddish brown colour on the filter paper.